Fundraising and Zakat Distribution in Poverty Alleviation in Maruthamunai, Sri Lanka: A Maqashid Sharia Perspective - Saujan, Iqbal; Rifas, Abi Huraira; Juhi, MS Fathima (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
In Sri Lanka, poverty has been one of the most pressing social issues over the past decade. This research examines zakat fundraising strategies and analyzes zakat distribution patterns in Maruthamunai, Sri Lanka, where Muslims constitute the dominant ethnic group. The current role of zakat in Maruthamunai is crucial in alleviating poverty. Primary data for this study included annual fundraising and distribution reports from the Zakat Fund, covering the years 2019 to 2023. As part of this qualitative research, unstructured interviews were conducted with the president, general secretary, deputy president, assistant secretary, members, and prominent individuals in the region. Data analysis was conducted using coding and is presented descriptively through the maqasid sharia approach. The results of this study indicate that the distribution of zakat funds in Maruthamunai has been less effective due to several factors, including insufficient receipt of zakat funds and inadequately structured internal distribution policies. Policymakers should focus on prioritizing the primary level of welfare needs (mashlahah dharuriyyah). Within this framework, the maqasid sharia perspective emphasizes the development of human resources as a priority over material development. Therefore, despite the relatively high poverty rate, the objectives of preserving religion, safeguarding human life, ensuring generational continuity, protecting intellect, and promoting wealth circulation can still be effectively pursued.